Estudo de marcadores inflamatórios em idosas deprimidas - Natália Silva Dias (2017)
The prevalence of major depressive disorder (MDD) in elderly people is around 7%. Inflammatory biomarkers imbalance have been associated with MDD. However, the inflammatory biomarkers imbalance in MDD in elderly patients remains unknown. The objective of this study was to evaluate the plasma concentration of inflammatory biomarkers (IL-6, IFN-, IFN-, TNF, IL-2, IL-4, IL-5, and IL-10) at MDD elderly patients in comparison with controls. We also evaluate whether there is any association between MDD in elderly people and demographic and clinical parameters. It was included 25 female MDD patients without other psychiatric disorders and 19 age and gender matched controls. All subject were evaluated by psychiatrists under MINI-Plus and HAM-D. It was collected also demographic data, the presence of clinical comorbidities and drugs. Cytokines were measured in plasma by immunoassay (Luminex® technology - Merck-Millipore®). IL-6 (p = 0.019) and IL-4 (p = 0.014) plasma levels are increased in MDD elderly in comparison with controls. There is a positive correlation between TNF (rho = 0.531; p = 0.003), IL-2 (rho = 0.366; p = 0.036), IL-5 (rho = 0.448; p = 0.012) and IL-10 (rho = 0.435; p = 0.015) plasma levels and the severity of depressive symptoms. MDD patients with mild depression presented lower TNF (p = 0.016), IL-5 (p = 0.012) and IL-10 (p = 0.037) plasma levels in comparison with MDD moderate/severe depression. The pro vs anti-inflammatory balance and the Th1 vs Th2 balance were maintained. Our results reinforce that MDD elderly patients also presented increased inflammatory markers.